Мембранотропна активність регуляторів росту рослин івіну та потейтину - Лозовий, В.П.; Ляхов, О.М.; Яблонська, С.В.; Філінська, О.М.; Рибальченко, Т.В. (Видавничий дім "Академперіодика" НАН України, 2008)
The influences of ivin (2,6-dimethylpyridine-N-oxie) and poteitin (molecular complex of 2,6-di-methylpyridine-N-oxide and succinate) on phospholipid monolayer model membranes that are composed of distearoyl phosphatidylcholine and natural phosphatidylcholine have been studied. It has been determined that ivin and poteitin change the energy parameters of monolayer membranes and raised the area size occupied by one phospholipid molecule. The interaction mechanism of the studied compounds with monolayer membranes does not depend on their saturation rate.